The hacker and the state: cyber attacks and the new normal of geopolitics - Buchanan, Ben (Harvard University Press, 2020)
Part one. Espionage: Exploiting home-field advantage -- Defeating encryption -- Building a backdoor -- Strategic espionage -- Counterintelligence -- Part two. Attack: Strategic sabotage -- Targeted disruption -- Coercion -- Testing and demonstration -- Part three. Destabilization: Election interference -- Exposure -- Theft, ransom, and manipulation -- Widespread disruption.